An exploration into the photo-transformation of the human form, through a research of its contemporary influential imagery and diversity within our culture - Murphy, Alexandra Christina (Rhodes University, Faculty of Humanities, Department of Fine Art, 1996)
The purpose of this study is to look at how the figure is imaged through the photographic medium today. Through this purpose I aim to explore the individual expression of the photographer in his photographic medium; the expression of the figure within the medium and the diverse practises of this medium in society - to build up an awareness and understanding of the diverse representations of the human form. The general aims of study are: 1 - to study how these three photographers choose to photograph the figure, through their technical, compositional and individual approach. 2 - to show how diverse the usage of the photographic figure is in the visual world. 3 - to expose an awareness of the photographic figure as transformation of an expression of self. 4 - to show the relationship between the photographer and the figure, the camera and the photographer, the camera and the figure, and the photographic figure and the viewer. 5 - to study my own photographic imagery in relation to the other imagery discussed. My research information was collected through: observations, discussions, literature and practical exploration. This study will attempt to draw conclusions, from its explorations, that will highlight the importance of the individual eye: that it is the individual eye that becomes the vehicle of transformation.
Keywords: Photography, Artistic; Photography of the nude; Human figure in art; Portrait photography